PEMANFAATAN LIMBAH IKAN LAUT BERNILAI EKONOMIS UNTUK KELESTARIAN LINGKUNGAN DESA MESKOM - Purnama Wirawan; Adyanata L Lubis; Firman Santosa (LPPM Universitas Bina Insan, 2026)
Meskom Village, Bengkalis Regency, is a coastal area where fisheries and seafood processing generate heads, bones, viscera, skin, scales, and trimming residues. When unmanaged, these organic materials deteriorate rapidly, create odour, increase pollution loads, and eliminate potential income. This study formulated a village-scale fish-waste utilization model, prioritized feasible products, and proposed an implementation pathway supporting environmental sustainability. An exploratory case study based on secondary data was conducted through literature synthesis, material-flow mapping, multicriteria assessment, and preliminary economic simulation. The criteria were technical simplicity, capital accessibility, market potential, environmental benefit, and social suitability. Liquid organic fertilizer and fish silage ranked first, with weighted scores of 4.80 and 4.60 on a five-point scale. Fish meal scored 3.75, fish oil 2.95, and collagen/gelatin 2.75. Under a 100 kg waste-per-cycle scenario, liquid fertilizer and silage showed higher revenue-to-cost ratios than fish meal; however, these values are planning simulations requiring validation through pilot production and local price surveys. The model emphasizes source segregation, rapid processing, sanitation, mass-balance recording, quality testing, and group-based enterprise management. A phased approach can reduce organic waste leakage while creating additional income opportunities for coastal households.